APLIKASI VINEGAR NIRA LONTAR (Borassus flabellifer) UNTUK MENGHAMBAT HISTAMIN PADA IKAN CAKALANG (Katsuwonus pelamis) - Nur Rezqi Amaliah; Lahming Lahming; Andi Sukainah (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to determine the effect of skipjack fish immersion in palm lontar vinegar solution with different storage times at the level of histamine produced. The research design used was Randomized Block Design (RBD). The parameters tested were histamine levels and total mesophyll bacteria. The concentration of vinegar solution at each storage time which had the lowest histamine and the lowest total bacteria was 10% with an average value of 17.34 mg / kg histamine and 4.3 log cfu / ml total bacteria, but a concentration of 6% could inhibit histamine formation. Total mesophyll bacteria were positively correlated with histamine levels in fish, so mesophyll bacteria affected the increase in histamine produced.